(3GdeGFI GdeSjMjI aj GdUfGYI GdWHjIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh Sgd gPG gh GdcJGH GdChd ef cJHfG aj UfGYI GdWH , hbUOfG fJcde ajeG jLH JbOjeg bHd GdTQhY aj Yde GdWH eeG jchf eONdkG , hGddg JYGdi gh GdoeYjf s
(3BNQgG (B:s
(3hdGojSJgGf HgPG Gdaf ef GdWH , aEfg YXje GdeYhfI hgh GdWH GdQhMGfj HGdMbjbI Je gPG GdcJGH hGdMeO ddg deG gh Cgdg s
(3fSNI NGeSI hgj ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B216 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B331 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs